2022
DOI: 10.3390/ijerph19138100
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Women’s Knowledge about HPV Using BERT Text Summarization: An Online Randomized Study

Abstract: Despite the availability of online educational resources about human papillomavirus (HPV), many women around the world may be prevented from obtaining the necessary knowledge about HPV. One way to mitigate the lack of HPV knowledge is the use of auto-generated text summarization tools. This study compares the level of HPV knowledge between women who read an auto-generated summary of HPV made using the BERT deep learning model and women who read a long-form text of HPV. We randomly assigned 386 women to two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Table 1 summarizes the characteristics of the analyzed studies, including their setting, results, and conclusions. One study (n=1/89, 1.1%) was published in 2022 24 , 84 (n=84/89, 94.4%) in 2023 13,25107 , and 4 (n=4/89, 4.5%) in 2024 108111 (all of which were peer-reviewed publications of preprints published in 2023). Most studies were quantitative non-randomized (n=84/89, 94.4%) 13,2527,29101,103,104,106,107,109111 , 4 (n=4/89, 4.5%) 28,102,105,108 had a qualitative study design, and one (n=1/89, 1.1%) 24 was quantitative randomized according to the MMAT 2018 criteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 summarizes the characteristics of the analyzed studies, including their setting, results, and conclusions. One study (n=1/89, 1.1%) was published in 2022 24 , 84 (n=84/89, 94.4%) in 2023 13,25107 , and 4 (n=4/89, 4.5%) in 2024 108111 (all of which were peer-reviewed publications of preprints published in 2023). Most studies were quantitative non-randomized (n=84/89, 94.4%) 13,2527,29101,103,104,106,107,109111 , 4 (n=4/89, 4.5%) 28,102,105,108 had a qualitative study design, and one (n=1/89, 1.1%) 24 was quantitative randomized according to the MMAT 2018 criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 (n=18/89, 20.2%) studies reported the presence of conflicts of interest and funding. 13,24,38,40,54,58,59,67,6971,74,80,84,96,103,105,111 Most studies did not report information about the institutional review board (IRB) approval (n=55/89, 61.8%) or deemed IRB approval unnecessary (n=28/89, 31.5%). Six studies obtained IRB approval (n=6/89, 6.7%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations